Contaminación de carne molida con cepas de Escherichia coli shigatoxigénico (STEC) provenientes de comercios minoristas de San Martín, Buenos Aires, categorizados según nivel socioeconómico - Miccio, L. (2011)
Shiga toxin-producing Escherichia coli (STEC) causes foodborne diseases, from mild diarrhea to hemolytic uremic syndrome which impact in Argentina. Many human infections were acquired from eating undercooked contaminated beef. The contamination of ground beef and their relation to socio-economic strata has not been studied. The aim of this study was to identify STEC in meat samples and establish virulence profi le, considering the socio-economic area of origin and persistence of contamination in local sales. It was selected 30% of the butcher shop of each socioeconomic level. It was analyzed 72 samples from 36 butcher shop of San Martín, Buenos Aires, in two independent sampling using multiplex PCR for stx1/stx2 and immunocapture for O157 at screening. Eleven strains were obtained from 26 suspect samples, 7% of the isolates were STEC O157. The weighted proportion of contamination was higher in the middle and low strata. Contamination from butcher shops was not persistent in both sampling. The degree of contamination by STEC in meat and the virulence of isolates were high for the study area. In view of this it is necessary to implement programs which help to reduce risks in public health.